Fast Motion Estimation using Modified Unsymmetrical Cross MultiHexagon Grid Search Algorithms for Video Coding Techniques - Sudhakar, R; Kuppusamy, P; Rao, PV Venkateswara (International Journal of Computer Sciences and Engineering, 2019)
Advanced digital video compression technologies have become an essential part of motion estimation strategy. The motion estimation of H.264/AVC is a tedious procedure. Numerous calculations were proposed for the video stream motion estimation, however they have a high computational multifaceted nature which altogether expands the encoder unpredictability. Video compression encoding computerized video to take up less storage space and transmission data transfer capacity. This paper proposes the Modified Unsymmetrical-Cross Multi Hexagon-Grid Search (MUMHexagonS) algorithm is utilized for motion estimation searching process .The conventional search patterns are replaced by the Asymmetrical Improved Cross Search Pattern, Minimized square search and Improved Diamond Search Pattern. The proposed motion estimation and video compression system lessen the movement estimation time, compression time, calculation cost and it accomplishes the better encoding effectiveness and great video quality.